(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This research aimed to identify how English basic skills play a role in conducting English debate and the significance is the influence of the English basic skills on debate performance. The research method used are descriptive qualitative. The participants of this research were 15 respondents from HIEST (Himsi English Debaters) community. The research data collecting technique used are interview and questionnaire. The data were then analyzed by using data reduction, data display, and conclusion drawing. The findings showed that, in conducting debate, English basic skills play a role as supporting skills to support other factors such as intelligence, and critical thinking. Mastering English basic skills also significantly influence the debate performance. When debaters have a good English basic skills, it would provide debaters to speak more, and receive argument more for the successful in arguing that would lead to reach the goals of the debate.